Handgrip Strength: Normative Reference Values in Males and Females Aged 6–64 Years Old in a Colombian Population - Garcia-Hermoso, A (Elsevier Ltd, 2021)
Background: Handgrip strength (HGS) is an indicator of overall strength; therefore, individual HGS measurements should be interpreted using geographic region and ethnic group references. Aims: The aim of this study was to develop new normative values for absolute and relative HGS in the Colombian population after stratification by sex, age, and body mass using the large National Representative Nutrition Survey 2015. Methods: This cross-sectional study included 3803 subjects aged 6–64 years. Absolute HGS was measured using a hand dynamometer with an adjustable grip, and normalized HGS was calculated by dividing the HGS by body mass. Smoothed centile tables for the P3, P10, P25, P50, P75, P90, and P97 centiles were calculated using Cole s lambda-mu-sigma (LMS) method. This study used a cutoff at 2 standard deviations (SDs) below the sex-specific peak mean value across the life course to define weak, absolute and relative HGS. Results: In men, HGS peaked at 26–33 years of age (~43.0 kg in P50), especially in the upper centiles, and fell away quickly. The pattern was different in females, where this value peaked at ages 25–33 (~26.0 kg in P50). We found a curvilinear pattern for HGS that declined with age in both sexes. There was significant variation in the slope for HGS in men and women around the age of 25 and 35 years, respectively. Conclusion: The normative values presented here are a valuable source of information for the clinical assessment of HGS and for comparison with studies from other countries. © 2021 European Society for Clinical Nutrition and Metabolism